2018
DOI: 10.1089/lgbt.2017.0145
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Expectancies, Heavy Drinking, and Indicators of Alcohol Use Disorders in a Community-Based Sample of Lesbian and Bisexual Women

Abstract: These findings suggest that alcohol expectancies are an important factor in determining risk for alcohol misuse/abuse among lesbian and bisexual women that could inform prevention, intervention, and treatment efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…were associated with alcohol abuse and dependency, whereas expecting that drinking will help you forget your worries when depressed was associated with heavy episodic drinking (Fish & Hughes, 2018). Research investigating victimization and bullying (Lereya, Copeland, Zammit, & Wolke, 2015) may benefit from testing the role of different anticipatory emotions as these might influence outcomes of aggression (anticipation of anger) relative to poor mental health (anticipation of anxiety).…”
Section: How Rejection Sensitivity Might Expand Understandings Of Lgbmentioning
confidence: 99%
“…were associated with alcohol abuse and dependency, whereas expecting that drinking will help you forget your worries when depressed was associated with heavy episodic drinking (Fish & Hughes, 2018). Research investigating victimization and bullying (Lereya, Copeland, Zammit, & Wolke, 2015) may benefit from testing the role of different anticipatory emotions as these might influence outcomes of aggression (anticipation of anger) relative to poor mental health (anticipation of anxiety).…”
Section: How Rejection Sensitivity Might Expand Understandings Of Lgbmentioning
confidence: 99%
“…differences in alcohol use. 12,35,36 Ultimately, a focus on the mechanisms that contribute to trends in SMY alcohol use will be critical for understanding ways to improve sexual minority health.…”
Section: Fish and Baamsmentioning
confidence: 99%
“…We may, for example, see different associations between RS and externalizing or internalizing behaviors as a result of anticipatory responses that reflect anger relative to anxiety. In a study among lesbian and bisexual women, for example, results showed that drinking expectancies of aggression and anger were associated with alcohol abuse and dependency, whereas expecting that drinking will help you forget your worries when depressed was associated with heavy episodic drinking (Fish & Hughes, 2018 ). Research investigating victimization and bullying (Lereya, Copeland, Zammit, & Wolke, 2015 ) may benefit from testing the role of different anticipatory emotions as these might influence outcomes of aggression (anticipation of anger) relative to poor mental health (anticipation of anxiety).…”
Section: How Rejection Sensitivity Might Expand Understandings Of Lgbmentioning
confidence: 99%